Gambaran Tingkat Pengetahuan dan Sikap Pencegahan HIV/AIDS pada Ibu Rumah Tangga di Desa Kroyo Karangmalang Sragen - Yudistika Alya Islami; Bagas Biyanzah Drajad Pamukhti (Pusat Riset dan Inovasi Nasional, 2025)
HIV/AIDS is a global health problem with a prevalence of 39.9 million cases and 40.4 million deaths worldwide by the end of 2022, of which 53% are women (World Health Organization, 2023). HIV cases in Indonesia continue to increase and are described as an iceberg phenomenon, with 70.2% of the spread occurring in the 25–49 age group and around 5,100 housewives infected each year, 35% of whom are infected from their partners. (Ministry of Health of the Republic of Indonesia, 2023). Objective; To find out the description of the level of knowledge and attitudes towards HIV/AIDS prevention among housewives in Kroyo Village, Karangmalang, Sragen. Method; The research method uses quantitative descriptive with cluster random sampling with a population of 323 housewives and a sample of 76 respondents. Results; The level of knowledge of HIV/AIDS among housewives in Kroyo Village, Karangmalang is mostly in the good category, namely 33 respondents or 43.3%. The attitude of HIV/AIDS prevention among housewives in Kroyo Village, Karangmalang is mostly in the positive category, namely 39 respondents or 51.3%. Conclusion; The majority of respondents had good knowledge and positive preventive attitudes about HIV/AIDS. Kata Kunci : Ibu Rumah Tangga, Pencegahan HIV/AIDS;Pengetahuan;Sikap